The Effect of Restorative Justice for Drug Users on The Overcapacity of Correctional Facility in Solo City - Diaz Ratna Iswara; Nugroho, Taufiq (Ajudikasi : Jurnal Ilmu Hukum, 2024)
The problem of drug abuse has become a major challenge in many countries, causing the number of prisoners addicted to narcotics to increase and causing overcrowding in prisons. This article discusses the influence of restorative justice as an innovative solution in dealing with drug users and overcrowding in correctional facility. Restorative justice replaces the traditional punishment-focused approach with one that is oriented towards rehabilitation, reconciliation, and the active participation of drug users in the rehabilitation process. In addition, restorative justice can help reduce overcrowding in prisons by reassessing the detention approach to drug users. Alternatives such as community-based rehabilitation programs and electronic monitoring could be implemented to alleviate pressure on the overcrowded prison system. By combining restorative justice and prison reform, governments can create more sustainable and humane solutions to the complex challenges of drug addiction.